Legal foundations for cooperation in the intellectual property domain within the Belt and road initiative - Leanovich, Elena B.; Hu, D. M. (Journal of the Belarusian State University. International Relations, 2022)
Intellectual property is studied in relation to the Belt and road initiative. The legal procedures and arrangements that maximise the economic benefits of regional cooperation are defined. Diverse and complex interrelationships between national and international intellectual property law are explored using the comparative legal research method. Key attention is drawn to the different levels of protection and enforcement of intellectual property rights in the context of the development of intellectual property systems in the participating countries. It is concluded that national intellectual property regimes retain objective distinguishing qualities. Recommendations for intellectual property disputes settlement are offered to provide countries and firm with a more transparent and accessible infrastructure in the multi-jurisdictional environment of the Belt and road initiative.
Keywords: Belt and road initiative; intellectual property rights; international intellectual property protection; economic interests; regional cooperation; China; territoriality of intellectual property